Why Individual Freedom and the Autonomy of Law Stand or Fall Together - Bjarne Melkevik; Åsbjørn Melkevik (Revista Acadêmica, 2017)
There is, in legal philosophy, an ongoing debate about the autonomy of law, that is, about the extent to which law is distinguishable from some other phenomena. The dominant views, today, all understand law as fulfilling a certain instrumental role. Justice and efficacy, then,are probably the most common relational others to law. For example, it is common to say that the law should further a certain understanding of distributive justice – this is the view preferred by philosophers such as John Rawls and Ronald Dworkin. Others have argued for the efficacy of the law as with the law-and-economics approach most famously championed by Judges Frank Easterbrook and Richard Posner. This paper argues for a radically different understanding of the law, as it explains why the law should indeed be autonomous. The question, however, is not whether the law is actually autonomous or not – it is obviously not, as the law is too often the plaything of various lawgivers.